Post Separation of Plastic Waste: Better for the Environment and Lower Collection Costs - Elbert Dijkgraaf; Raymond Gradus (Tinbergen Institute, 2016)
The European Union (EU) advocates a plastic waste recycling rate of more than 55% through home separation by households. Even for the Netherlands, which has already invested heavily in plastic recycling policies, there is still a challenge to meet this target. We show that post separation is an advisable alternative with more separation of plastic waste and lower collection costs. Based on data for 2013-2014, Dutch municipalities with post-separation have 6.2 kilogram more plastic than municipalities with only bring locations. Moreover, the effectiveness of post separation increases significantly over time to 8.4 kilograms in 2014. Also curbside collection of plastic waste can be effective, if it is combined with an unit-based pricing system, but in such a case the collection costs are higher. Therefore, there are indications that the cost effectiveness of recycling plastic waste increases, if post separation is chosen.
Keywords: H43; Q38; Q42; 330; plastic waste; recycling; post separation; home separation; cost effectiveness